CONTRIBUTIONS REGARDING IMPACT ON THE NATURAL ENVIRONMENT OF A NUCLEAR EQUIPMENT BULIDING COMPANY - Gheorghe AMZA; Dan Florin NIXOI; Andrei DIMITRESCU; Zoia APOSTOLESCU; Gabriel Dan TAŞCa; Marius Cornel TEODORESCU (Fiabilitate şi Durabilitate, 2016)
Paper presents how to determine the environmental impact of nuclear equipment manufacturingcompany. Here are analized the most important sources of environmental pollution (booth blast, furnace annealing and thermal plant) and principal emissions and pollutants of the environment are determined in five distinct points within 200 m of the enterprise, using a measuring original stand. According practical determination, CO,SO2 and NO2, concentrations exceed normal values presented in the 462/93 Government Order.